High-thermal-conductivity ultrathin silica gel gasket as well as preparation method and application thereof

By using the combination of small-particle-modified aluminum nitride and alumina as thermal conductivity filler, combined with specific silicone oil and process treatment, a high-thermal conductivity ultra-thin silicone gasket was prepared, which solved the problems of low thermal conductivity and excessive thickness in the prior art, and achieved efficient heat dissipation effect of electronic products.

CN119912819APending Publication Date: 2025-05-02SHANDONG SINOCERA FUNCTIONAL MATERIAL CO LTD

Patent Information

Application Number
CN202510193556.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-21
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The existing high-thermal conductivity silicone gaskets have too high thickness and the ultra-thin thermal conductivity is relatively low, making it difficult to meet the efficient heat dissipation needs of electronic products under the trend of miniaturization.

Method used

A combination of small-particle-modified aluminum nitride and alumina is used as a thermal filler, and combined with high-temperature, low-volatilization vinyl silicone oil and hydrogen-containing silicone oil, a high-thermal conductivity ultra-thin silicone gasket is prepared through specific ratios and process treatments.

Benefits of technology

It realizes the high thermal conductivity and ultra-thin structure of thermal conductivity silicone gaskets, with thermal conductivity up to 8W/m·K, which solves the problems of low thermal conductivity and excessive thickness, and expands its application scenarios in electronic products.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a high-heat-conductivity ultrathin silica gel gasket and a preparation method and application thereof, and relates to the technical field of heat conduction interface materials.According to the high-heat-conductivity ultrathin silica gel gasket, high-temperature-resistant and low-volatility vinyl silicone oil, hydrogen-containing silicone oil and side hydrogen-containing silicone oil are used in cooperation with a modifier, an inhibitor and an antioxidant, and the high-heat-conductivity ultrathin silica gel gasket is prepared. Through combination of specific raw materials in a specific ratio, high filling of the heat-conducting filler is realized, and the gasket is endowed with good high temperature resistance and low volatile matter performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of thermal conductive interface materials, and in particular to a high thermal conductive ultra-thin silicone gasket and a preparation method and application thereof. Background Art

[0002] Thermally conductive silicone gasket is a thermally conductive interface material made of silicone as the base material and by adding thermally conductive fillers such as metal oxides using a special process. Thermally conductive silicone gasket has excellent thermal conductivity and can be filled in the gaps between components to connect heating components with heat dissipation components, effectively improving heat transfer efficiency and improving component heating conditions. It is widely used in electronic devices.

[0003] With the continuous advancement of science and technology, electronic products are gradually developing in the direction of diversification and miniaturization, pursuing a thinner and lighter body, and the size of electronic components is constantly shrinking. However, while pursuing miniaturization, in order to ensure that the performance and function of the product are not affected, the requirements for heat dissipation of electronic components are also increasing. Ultra-thin thermal conductive gaskets have a smaller volume, do not take up too much space, and can better adapt to the trend of miniaturization of electronic products. In addition, as an important performance indicator of thermal conductive silicone gaskets, thermal resistance reflects the thermal conductivity of the material. The greater the thermal resistance, the worse the thermal conductivity of the entire material. Therefore, it is very important to reduce the thermal resistance of thermal conductive silicone gaskets. The research results show that the thermal resistance of the material is closely related to its thermal conductivity and thickness. Under the same thermal conductivity, the smaller the thickness, the smaller the thermal resistance. Therefore, ultra-thin thermal conductive gaskets have certain advantages in applications. However, most of the high thermal conductivity silicone gaskets currently on the market have a thickness of 0.3mm or more. In addition, the thermal conductivity of most ultra-thin thermal conductive silicone gaskets is not high (1-3W / m·K), which leads to certain limitations in actual application scenarios.

[0004] In order to achieve a high thermal conductivity coefficient of an insulating heat-conducting silicone gasket, the prior art provides a method of using aluminum nitride and aluminum oxide as a thermally conductive filler. CN 111925654 B discloses a large-particle aluminum nitride and aluminum oxide compounded thermally conductive insulating silicone material and a preparation method thereof. The thermally conductive filler used in the method is a combination of aluminum nitride particles and aluminum oxide particles, wherein the particle size of the aluminum nitride particles is 20-100 μm, the particle size of the aluminum oxide particles is 1-30 μm, and the particle size of the aluminum nitride particles is larger than the particle size of the aluminum oxide particles. The specific preparation method is to compound the aluminum nitride particles with the aluminum oxide particles, add a surfactant and heat and mix to obtain a thermally conductive filler, and then add the thermally conductive filler to a mixture of polydimethylsiloxane, hydrogen-containing silicone oil, dimethyl silicone oil, and an inhibitor, and after fully stirring, add a catalyst and stir evenly to obtain an insulating heat-conducting silicone material. In the specific implementation case provided, the sample thickness obtained by the method is 1.5 mm, which cannot be used to prepare an ultra-thin thermally conductive gasket with a thickness of less than 0.15 mm. Therefore, there is a need in the art to develop an ultra-thin thermally conductive silicone gasket with high thermal conductivity to expand its application in electronic products and other fields.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The purpose of the present invention is to provide an ultra-thin thermally conductive silicone gasket with high thermal conductivity and a preparation method thereof, so as to solve the problems that the current high thermally conductive silicone gasket is too thick and the ultra-thin thermally conductive gasket has low thermal conductivity.

[0007] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0008] The invention provides a high thermal conductivity ultra-thin silicone gasket, which comprises, by weight: 100 parts of vinyl silicone oil, 5-30 parts of end hydrogen-containing silicone oil, 100-150 parts of side hydrogen-containing silicone oil, 20-100 parts of modifier, 500-1500 parts of aluminum nitride, 200-3500 parts of aluminum oxide, 0.2-0.4 parts of inhibitor, 0.5-5 parts of catalyst, 4-10 parts of antioxidant, 2-10 parts of dispersant and 0.5-2 parts of optional colorant.

[0009] Furthermore, the composition comprises, by weight: 100 parts of vinyl silicone oil, 22 parts of end hydrogen-containing silicone oil, 137 parts of side hydrogen-containing silicone oil, 40 parts of modifier, 820 parts of aluminum nitride, 2870 parts of aluminum oxide, 0.2-1.5 parts of inhibitor, 5 parts of catalyst, 4 parts of antioxidant, 4 parts of dispersant and 1 part of optional colorant.

[0010] Furthermore, the modifier is at least one of hydroxyl-terminated polydimethylsiloxane, vinyl-terminated polydimethylsiloxane and alkoxy-terminated polydimethylsiloxane.

[0011] Further, the aluminum oxide includes aluminum oxide A, aluminum oxide B and aluminum oxide C;

[0012] The aluminum oxide A is spherical aluminum oxide with a particle size of 20-40 μm, the aluminum oxide B is single-crystal aluminum oxide with a particle size of 1-20 μm, and the aluminum oxide C is single-crystal aluminum oxide with a particle size of 0.5-1 μm;

[0013] Optionally, the average particle size of the aluminum nitride is 1-5 μm.

[0014] Furthermore, the viscosity of the vinyl silicone oil is 100-500 cP, and the vinyl content is 0.5-1.5 wt %;

[0015] Optionally, the viscosity of the hydrogen-containing silicone oil is 400-1000 mm 2 / s, the hydrogen content accounts for 0.01-0.03% of the weight of the hydrogen-containing silicone oil;

[0016] Optionally, the viscosity of the side hydrogenated silicone oil is 90-130 mm 2 / s, and the hydrogen content accounts for 0.1-0.3% of the weight of the hydrogen-containing silicone oil.

[0017] Further, the inhibitor includes an acetylenic alcohol inhibitor;

[0018] Optionally, the catalyst comprises a platinum catalyst;

[0019] Optionally, the antioxidant is a hindered phenol antioxidant, preferably one or more of antioxidant 1010, antioxidant 1024 and antioxidant 1076;

[0020] Optionally, the dispersant includes a polymer dispersant;

[0021] Optionally, the colorant includes black silicone rubber color paste.

[0022] The present invention also provides a method for preparing the above-mentioned high thermal conductivity ultra-thin silicone gasket, comprising the following steps:

[0023] (a) mixing a formulated amount of vinyl silicone oil, terminal hydrogen silicone oil, side hydrogen silicone oil, inhibitor, catalyst, antioxidant, dispersant and optional colorant to prepare an organic silica gel matrix;

[0024] (b) adding a formula amount of aluminum nitride and aluminum oxide to the organic silica gel matrix and stirring, and adding a formula amount of a modifier during the stirring process to obtain a base material;

[0025] (c) The base material is calendered and formed to obtain the high thermal conductivity ultra-thin silicone gasket.

[0026] Furthermore, before step (c), the method further includes the steps of strengthening mixing of the base material and removing gas;

[0027] Preferably, a three-roll mill is used to enhance mixing;

[0028] Preferably, the gas is removed by vacuuming.

[0029] Further, the step (c) includes a primary calendering and a secondary calendering;

[0030] Preferably, the thickness of the base material after the first calendering is 0.20 mm-0.25 mm;

[0031] Preferably, the thickness of the base material after the secondary calendering is 0.08mm-0.16mm;

[0032] Optionally, the molding temperature is 120-180°C, preferably 150°C.

[0033] In addition, the present invention also provides the above-mentioned high thermal conductivity ultra-thin silicone gasket and the use of the high thermal conductivity ultra-thin silicone gasket prepared by the above-mentioned preparation method in electronic products.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] The high thermal conductivity ultra-thin silicone gasket provided by the present invention adopts high temperature resistant, low volatility vinyl silicone oil, hydrogen-containing silicone oil and side hydrogen-containing silicone oil, and is used in combination with a modifier, an inhibitor and an antioxidant. Through a combination of specific raw materials in a specific ratio, a high filling of thermal conductive filler is achieved, and the gasket is endowed with good high temperature resistance and low volatility performance. DETAILED DESCRIPTION

[0036] Unless otherwise defined herein, scientific and technical terms used in conjunction with the present invention shall have the meanings commonly understood by those of ordinary skill in the art. The meaning and scope of the terms should be clear, however, in the case of any potential ambiguity, the definitions provided herein take precedence over any dictionary or external definitions. In this application, unless otherwise stated, the use of "or" means "and / or". In addition, the use of the term "including" and other forms is non-limiting.

[0037] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] Based on the problem of insufficient thermal conductivity of ultra-thin silicone gaskets, the present invention proposes to use silicone rubber as a base material and a combination of small-particle modified aluminum nitride and aluminum oxide as a thermal conductive filler to prepare a high thermal conductivity ultra-thin silicone gasket.

[0039] According to a first aspect of the present invention, a high thermal conductivity ultra-thin silicone gasket is provided, which comprises, by weight: 100 parts of vinyl silicone oil, 5-30 parts of end hydrogen-containing silicone oil, 100-150 parts of side hydrogen-containing silicone oil, 20-100 parts of modifier, 500-1500 parts of aluminum nitride, 200-3500 parts of aluminum oxide, 0.2-0.4 parts of inhibitor, 0.5-5 parts of catalyst, 4-10 parts of antioxidant, 2-10 parts of dispersant and 0.5-2 parts of optional colorant.

[0040] The present invention uses high temperature resistant, low volatility vinyl silicone oil, hydrogen-containing silicone oil and side hydrogen-containing silicone oil, in combination with modifiers, inhibitors and antioxidants, to achieve high filling of thermal conductive fillers and give the gasket good high temperature resistance and low volatility properties.

[0041] Vinyl silicone oil

[0042] The vinyl silicone oil is a double-terminal vinyl silicone oil, and its molecular structure is CH 2 =CH-Si(CH 3 ) 2 O[(CH 3 ) 2 SiO] n (CH 3 ) 2 Si-CH=CH 2 ;

[0043] In some preferred embodiments, the viscosity of the vinyl silicone oil is 100-500 cP, for example, but not limited to 100 cP, 200 cP, 300 cP, 400 cP or 500 cP, and the content of vinyl is 0.5-1.5 wt%, for example, but not limited to 0.5 wt%, 0.8 wt%, 1 wt%, 1.2 wt% or 1.5 wt%. The preferred viscosity is 100 cP. The lower viscosity of the silicone oil can increase the wettability of the base material, which is beneficial to the surface state of the sample after calendering.

[0044] Hydrogenated silicone oil

[0045] The hydrogen-terminated silicone oil is hydrogen-terminated polydimethylsiloxane, and its structural formula is H-Si(CH 3 ) 2 -O-(Si(CH 3 ) 2 -O) n -Si(CH 3 )2 -H. Its content can be, for example, but not limited to, 5 parts, 8 parts, 10 parts, 15 parts, 20 parts, 25 parts or 30 parts.

[0046] In some preferred embodiments, the viscosity of the hydrogen-terminated silicone oil is 400-1000 mm 2 / s, for example, but not limited to 400mm 2 / s、500mm 2 / s、600mm 2 / s、700mm 2 / s、800mm 2 / s、900mm 2 / s or 1000mm 2 / s, the hydrogen content accounts for 0.01-0.03% of the weight of the hydrogen-containing silicone oil, for example, it can be, but not limited to, 0.01%, 0.02% or 0.03%. The preferred viscosity is 400mm 2 / s.

[0047] Side hydrogen silicone oil

[0048] The side hydrogen-containing silicone oil is polydimethylmethylhydrogensiloxane, and its structural formula is (CH 3 ) 3 SiO[(CH 3 ) 2 SiO] m [CH 3 HSiO] n Si(CH 3 ) 3 The content thereof may be, for example, but not limited to, 100 parts, 110 parts, 120 parts, 130 parts, 140 parts or 150 parts.

[0049] In some preferred embodiments, the viscosity of the side hydrogen silicone oil is 90-130 mm 2 / s, for example, but not limited to 90mm 2 / s、100mm 2 / s, 110mm 2 / s, 120mm 2 / s or 130mm 2 / s; the hydrogen content accounts for 0.1-0.3% of the weight of the hydrogen-containing silicone oil, for example, but not limited to 0.1%, 0.2% or 0.3%. The preferred viscosity is 90mm 2 / s.

[0050] Modifier

[0051] The content of the modifier may be, for example, but not limited to, 20 parts, 30 parts, 40 parts, 50 parts, 60 parts, 70 parts, 80 parts, 90 parts or 100 parts.

[0052] In some preferred embodiments, the modifier is at least one of hydroxy-terminated polydimethylsiloxane, vinyl-terminated polydimethylsiloxane and alkoxy-terminated polydimethylsiloxane. The above-mentioned specific modifier has high temperature resistance and low volatility, and can effectively improve the service life of the gasket. At the same time, the above-mentioned specific modifier can be directly added during the gasket production process, which is different from the commonly used silane coupling agents such as γ-methacryloxypropyltrimethoxysilane (KH570) and n-dodecyltrimethoxysilane, and does not require pH adjustment, hydrolysis and high temperature pretreatment.

[0053] Thermally conductive fillers

[0054] The thermally conductive filler in the present invention includes aluminum nitride and aluminum oxide. The content of aluminum nitride may be, for example, but not limited to 500 parts, 800 parts, 1000 parts, 1200 parts or 1500 parts; the content of aluminum oxide may be, for example, but not limited to 200 parts, 500 parts, 1000 parts, 2000 parts, 3000 parts or 3500 parts.

[0055] In some preferred embodiments, the alumina includes alumina A, alumina B and alumina C; the alumina A is a spherical alumina with a particle size of 20-40 μm, the alumina B is a single crystal alumina with a particle size of 1-20 μm, and the alumina C is a single crystal alumina with a particle size of 0.5-1 μm; the particle size of the thermal conductive filler has a significant effect on the thermal conductivity and thermal resistance of the thermal conductive silicone gasket. The thermal conductivity of the sample prepared using a single powder filler is poor. Reasonable powder grading, that is, the combination of powders of different particle sizes can improve the fluidity and density of the material, thereby improving the thermal conductivity of the gasket and reducing the thermal resistance. At the same time, the type, shape, size and density of the powder have a great influence on the powder grading effect. When making an ultra-thin thermal conductive silicone gasket, the proportion of 20-40 μm alumina in the above-mentioned particle size powder should not exceed 50%, otherwise it will cause too many gasket defects. Powders with too high specific surface areas such as aluminum nitride and alumina C should not be too much, otherwise the base material will be too dry and cannot be rolled.

[0056] In some preferred embodiments, the average particle size of the aluminum nitride is 1-5 μm.

[0057] By using small-particle thermal conductive fillers, the thickness of the thermal conductive silicone gasket prepared by the present invention can be as low as 0.08mm-0.16mm, and it has a certain strength and is convenient for mounting and use. By adjusting the grading of powders with different particle sizes and the filling quality of the fillers, the high thermal conductivity of the ultra-thin gasket can be achieved.

[0058] Inhibitors

[0059] The content of the inhibitor may be, for example, but not limited to, 0.2 parts, 0.5 parts, 1 part or 1.5 parts.

[0060] In some preferred embodiments, the inhibitor includes an alkynol inhibitor, and typical inhibitors may be 1-ethynylcyclohexanol, 3,7,11-trimethyldodecyn-3-ol, 3-methyl-1-dodecyn-3-ol, 3,5-dimethyl-1-hexyn-3-ol, and the like.

[0061] catalyst

[0062] The content of the catalyst may be, for example, but not limited to, 0.5 parts, 1 part, 2 parts, 3 parts, 4 parts or 5 parts.

[0063] In some preferred embodiments, the catalyst comprises a platinum catalyst.

[0064] Antioxidants

[0065] The content of the antioxidant may be, for example, but not limited to, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts or 10 parts.

[0066] In some preferred embodiments, the antioxidant is a hindered phenol antioxidant, preferably one or more of antioxidant 1010, antioxidant 1024 and antioxidant 1076.

[0067] Dispersants

[0068] The content of the dispersant may be, for example, but not limited to, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts or 10 parts.

[0069] In some preferred embodiments, the dispersant includes a polymer dispersant, and typical dispersants may be block polymer dispersants, anionic polymer dispersants, nonionic polymer dispersants, and the like.

[0070] Pigments

[0071] The content of the colorant may be, for example, but not limited to, 0.5 parts, 1 part, 1.5 parts or 2 parts.

[0072] In some preferred embodiments, the colorant includes black silicone rubber color paste.

[0073] It is to be understood that the term "optional" in the present invention means that the formula may or may not contain colorants, and that colorants may or may not be added according to actual needs during use. Whether or not colorants are added is within the scope of protection of the present invention, and the present invention does not make any specific limitations on this.

[0074] The vinyl silicone oil and hydrogen silicone oil used in the preparation of the high thermal conductivity ultra-thin silicone gasket of the present invention are both low-viscosity silicone oils, and the inorganic thermal conductive filler is surface-modified with modified polydimethylsilicone oil. Under normal circumstances, the use of large-particle powder in the formula can effectively reduce the viscosity of the material and improve the thermal conductivity of the gasket. Since the gasket is extremely thin, in order to ensure the state and thermal conductivity of the sample, the particle size of the thermal conductive powder should not be too large. The ultra-thin thermal conductive silicone gaskets prepared in this experiment are all graded with small-particle powders, and the maximum particle size of the powder is below 40μm. The high viscosity of the silicone oil and the lack of powder modification cannot achieve high filling of the material, and thus cannot achieve high thermal conductivity of the sample; in addition, the powder modifier used in this experiment can be directly added during the gasket production process, which is different from the commonly used silane coupling agents such as γ-methacryloxypropyltrimethoxysilane (KH570) and n-dodecyltrimethoxysilane, and does not require pH adjustment, hydrolysis, and high-temperature pretreatment. At the same time, the modifier has high temperature resistance and low volatility. When used with an antioxidant, it gives the gasket good high temperature resistance and increases the service life of the gasket.

[0075] According to a second aspect of the present invention, a method for preparing the above-mentioned high thermal conductivity ultra-thin silicone gasket is provided, comprising the following steps:

[0076] (a) mixing a formulated amount of vinyl silicone oil, terminal hydrogen silicone oil, side hydrogen silicone oil, inhibitor, catalyst, antioxidant, dispersant and optional colorant to prepare an organic silica gel matrix;

[0077] (b) adding a formula amount of aluminum nitride and aluminum oxide to the organic silica gel matrix and stirring, and adding a formula amount of a modifier during the stirring process to obtain a base material;

[0078] (c) The base material is calendered and formed to obtain the high thermal conductivity ultra-thin silicone gasket.

[0079] The present invention uses a method of directly adding a modifier to modify the surface of aluminum nitride and aluminum oxide during the production process. There is no need to hydrolyze the modifier and pre-treat the powder at high temperature. When used in conjunction with low-viscosity silicone oil and a dispersant, an ultra-high mass filling rate can be achieved in the silicone rubber system. A high thermal conductivity coefficient is achieved by finely screening the thermal conductive filler and adjusting the powder gradation. According to tests, the thermal conductivity coefficient can reach 8W / m·K, which solves the problem of low thermal conductivity of ultra-thin thermal conductive silicone gaskets and expands their application scenarios.

[0080] In some preferred embodiments, before step (c), the steps of strengthening mixing and removing gas from the base material are also included in sequence;

[0081] Preferably, a three-roll mill is used to enhance mixing;

[0082] Preferably, the gas is removed by vacuuming.

[0083] In some preferred embodiments, step (c) includes primary calendering and secondary calendering;

[0084] Preferably, the thickness of the base material after the first calendering is 0.20 mm-0.25 mm;

[0085] Preferably, the thickness of the base material after the secondary calendering is 0.08mm-0.16mm;

[0086] Optionally, the molding temperature is 120-180°C, preferably 150°C.

[0087] In some specific embodiments, the method for preparing the high thermal conductivity ultra-thin thermal conductive insulating gasket comprises the following steps in sequence:

[0088] (1) Preparation of organic silica gel matrix: 100 parts of vinyl silicone oil, 15-30 parts of end hydrogen silicone oil, 100-150 parts of side hydrogen silicone oil, 0.1-2 parts of inhibitor, 0.2-5 parts of catalyst, 0.1-2 parts of colorant, 4-10 parts of antioxidant, and 2-10 parts of dispersant are added into a rotary stirrer and stirred at a speed of 900 rpm for 10 minutes to obtain an organic silica gel matrix;

[0089] (2) Powder screening: The aluminum oxide and aluminum nitride powders are finely screened using sieves with different apertures according to their particle sizes.

[0090] (3) Mixing an organic silica gel matrix with an inorganic filler: adding 500-1500 parts of sieved aluminum nitride A, 1700-2200 parts of aluminum oxide A, 300-600 parts of aluminum oxide B and 500-800 parts of aluminum oxide C to an organic silica gel matrix, stirring at a speed of 900 rpm for 10-30 min, and gradually adding 20-100 parts of a modifier during the stirring process to obtain a base material;

[0091] (4) The stirred base material is thoroughly mixed by a three-roll mill, and then placed in a vacuum machine to evacuate the air in the base material;

[0092] (5) The vacuumed base material is placed between two release films and calendered by a calendering machine. The base material thickness is pressed to between 0.20 mm and 0.25 mm during the initial pressing. The base material thickness is controlled to between 0.08 mm and 0.16 mm during the secondary calendering. The base material is then molded at 150° C. to obtain a high thermal conductivity ultra-thin thermal insulating gasket.

[0093] The present invention is further described below by way of examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or directly purchased from the market.

[0094] Raw materials: vinyl silicone oil, end-containing hydrogen silicone oil, side-containing hydrogen silicone oil, Ningbo Runhe High-tech Materials Technology Co., Ltd. 3,5-dimethyl-1-hexyn-3-ol inhibitor, Macklin Chemical Reagent or 1-ethynylcyclohexanol, 3,7,11-trimethyldodecyn-3-ol, Guangzhou Siyou New Materials Technology Co., Ltd. Tetramethyl divinyl disiloxane platinum complex catalyst, Jiangxi Beiteli New Materials Co., Ltd. or PT-5000 platinum catalyst, Guangzhou Siyou New Materials Technology Co., Ltd. Black silicone rubber color paste, Shenzhen Yingxin Silicone Co., Ltd. Antioxidant 1076 or Antioxidant 1010, BASF. Anionic polymer dispersant, Zhonglian Federation.

[0095] Example 1

[0096] This embodiment provides a high thermal conductivity ultra-thin silicone gasket, which is prepared by the following method:

[0097] Vinyl silicone oil (500cP) 100 parts, end-hydrogen silicone oil (400-1000mm 2 / s) 22 parts, side hydrogen silicone oil (90-130mm 2 / s) 137 parts, 3,5-dimethyl-1-hexyn-3-ol inhibitor 1 part, tetramethyl divinyl disiloxane platinum complex catalyst 5 parts, black silicone rubber color paste 1 part, antioxidant 1076 4 parts, anionic polymer dispersant 4 parts are added to a rotary stirrer, and stirred at a speed of 900 rpm for 10 minutes to obtain an organic silica gel matrix. Finely screened 2μm aluminum nitride A 820 parts, 30μm aluminum oxide A 1700 parts, 10μm aluminum oxide B 520 parts and 1μm aluminum oxide C 650 parts are added to the organic silica gel matrix, stirred at a speed of 900 rpm for 10-30 minutes, and 40 parts of terminal hydroxyl polydimethylsiloxane are gradually added to obtain a base material. The stirred base material is fully mixed by a three-roll grinder, then placed in a vacuum machine to evacuate the air in the base material, and then placed between release films and calendered by a calender. The base material thickness is pressed to between 0.20mm during the initial pressing, and the base material thickness is controlled to 0.13mm during the secondary calendering. Then, it is formed at 150°C to obtain a high thermal conductivity ultra-thin thermal insulating gasket.

[0098] Example 2

[0099] This embodiment provides a high thermal conductivity ultra-thin silicone gasket, which is prepared by the following method:

[0100] 100 parts of vinyl silicone oil (100cP), end-hydrogen silicone oil (400-1000mm 2 / s) 21 parts, side hydrogen silicone oil (90-130mm 2 / s) 132 parts, 3,5-dimethyl-1-hexyn-3-ol inhibitor 1 part, tetramethyl divinyl disiloxane platinum complex 4 parts, black silicone rubber color paste 1 part, antioxidant 10764 parts, anionic polymer dispersant 4 parts are added to a rotary stirrer, and stirred at a speed of 900 rpm for 10 minutes to obtain an organic silica gel matrix. Finely screened 2μm aluminum nitride A 1200 parts, 30μm aluminum oxide A 1760 parts, 20μm aluminum oxide B 400 parts and 0.5μm aluminum oxide C 470 parts are added to the organic silica gel matrix, stirred at a speed of 900 rpm for 10-30 minutes, and 60 parts of terminal hydroxyl polydimethylsiloxane are gradually added to obtain a base material. The stirred base material is fully mixed by a three-roll grinder, then placed in a vacuum machine to evacuate the air in the base material, and then placed between release films and calendered by a calender. The base material thickness is pressed to between 0.20mm during the initial pressing, and the base material thickness is controlled to 0.12mm during the secondary calendering. Then, it is formed at 150°C to obtain a high thermal conductivity ultra-thin thermal insulating gasket.

[0101] Example 3

[0102] This embodiment provides a high thermal conductivity ultra-thin silicone gasket, which is prepared by the following method:

[0103] 100 parts of vinyl silicone oil (100cP), end-hydrogen silicone oil (400-1000mm 2 / s) 22 parts, side hydrogen silicone oil (90-130mm 2 / s) 139 parts, 3,5-dimethyl-1-hexyn-3-ol inhibitor 1 part, tetramethyl divinyl disiloxane platinum complex catalyst 3 parts, black silicone rubber color paste 1 part, antioxidant 1076 4 parts, anionic polymer dispersant 4 parts are added to a rotary stirrer, and stirred at a speed of 900 rpm for 10 minutes to obtain an organic silica gel matrix. Finely screened 2μm aluminum nitride A 1000 parts, 40μm aluminum oxide A 1700 parts, 5μm aluminum oxide B 560 parts and 0.5μm aluminum oxide C 450 parts are added to the organic silica gel matrix, stirred at a speed of 900 rpm for 10-30 minutes, and 60 parts of terminal hydroxyl polydimethylsiloxane are gradually added to obtain a base material. The stirred base material is fully mixed by a three-roll grinder, then placed in a vacuum machine to evacuate the air in the base material, and then placed between release films and calendered by a calender. The base material thickness is pressed to between 0.20mm during the initial pressing, and the base material thickness is controlled to 0.12mm during the secondary calendering. Then, it is formed at 150°C to obtain a high thermal conductivity ultra-thin thermal insulating gasket.

[0104] Example 4

[0105] This embodiment provides a high thermal conductivity ultra-thin silicone gasket, which is prepared by the following method:

[0106] Vinyl silicone oil (500cP) 100 parts, end-hydrogen silicone oil (400-1000mm 2 / s) 5 parts, side hydrogen silicone oil (90-130mm 2 / s) 150 parts, 3,5-dimethyl-1-hexyn-3-ol inhibitor 1 part, tetramethyl divinyl disiloxane platinum complex catalyst 5 parts, black silicone rubber color paste 2 parts, antioxidant 1076 4 parts, anionic polymer dispersant 10 parts are added to a rotary stirrer, and stirred at a speed of 900 rpm for 10 minutes to obtain an organic silica gel matrix. Finely screened 5μm aluminum nitride A 1500 parts, 20μm aluminum oxide A 120 parts, 20μm aluminum oxide B 30 parts and 0.5μm aluminum oxide C 50 parts are added to the organic silica gel matrix, stirred at a speed of 900 rpm for 10-30 minutes, and 20 parts of terminal hydroxyl polydimethylsiloxane are gradually added to obtain a base material. The stirred base material is fully mixed by a three-roll grinder, then placed in a vacuum machine to evacuate the air in the base material, and then placed between release films and calendered by a calender. The base material thickness is pressed to between 0.20mm during the initial pressing, and the base material thickness is controlled to 0.13mm during the secondary calendering. Then, it is formed at 150°C to obtain a high thermal conductivity ultra-thin thermal insulating gasket.

[0107] Example 5

[0108] This embodiment provides a high thermal conductivity ultra-thin silicone gasket, which is prepared by the following method:

[0109] Vinyl silicone oil (500cP) 100 parts, end-hydrogen silicone oil (400-1000mm 2 / s) 30 parts, side hydrogen silicone oil (90-130mm 2 / s) 100 parts, 3,5-dimethyl-1-hexyn-3-ol 1 part, tetramethyl divinyl disiloxane platinum complex catalyst 0.5 parts, black silicone rubber color paste 0.5 parts, antioxidant 1076 10 parts, anionic polymer dispersant 2 parts are added to a rotary stirrer, and stirred at a speed of 900 rpm for 10 minutes to obtain an organic silica gel matrix. Finely screened 1μm aluminum nitride A 500 parts, 40μm aluminum oxide A 2000 parts, 1μm aluminum oxide B 600 parts and 1μm aluminum oxide C 900 parts are added to the organic silica gel matrix, stirred at a speed of 900 rpm for 10-30 minutes, and 100 parts of terminal hydroxyl polydimethylsiloxane are gradually added to obtain a base material. The stirred base material is fully mixed by a three-roll grinder, then placed in a vacuum machine to evacuate the air in the base material, and then placed between release films and calendered by a calender. The base material thickness is pressed to between 0.20mm during the initial pressing, and the base material thickness is controlled to 0.13mm during the secondary calendering. Then, it is formed at 150°C to obtain a high thermal conductivity ultra-thin thermal insulating gasket.

[0110] Comparative Example 1

[0111] This comparative example provides a high thermal conductivity ultra-thin silicone gasket, which is prepared by the following method:

[0112] Vinyl silicone oil (500cP) 100 parts, end-hydrogen silicone oil (400-1000mm 2 / s) 22 parts, side hydrogen silicone oil (90-130mm 2 / s) 137 parts, 3,5-dimethyl-1-hexyn-3-ol inhibitor 1 part, tetramethyl divinyl disiloxane platinum complex catalyst 5 parts, black silicone rubber color paste 1 part, antioxidant 1076 4 parts, anionic polymer dispersant 4 parts are added to a rotary stirrer, and stirred at a speed of 900 rpm for 10 minutes to obtain an organic silica gel matrix. Finely screened 2μm aluminum nitride A 820 parts, 30μm aluminum oxide A 1700 parts, 10μm aluminum oxide B 520 parts and 1μm aluminum oxide C 650 parts are added to the organic silica gel matrix, and stirred at a speed of 900 rpm for 10-30 minutes to obtain a base material. The stirred base material is fully mixed by a three-roll grinder, then placed in a vacuum machine to evacuate the air in the base material, and then placed between release films and calendered by a calender. The base material thickness is pressed to between 0.20mm during the initial pressing, and the base material thickness is controlled to 0.13mm during the secondary calendering. Then, it is formed at 150°C to obtain a high thermal conductivity ultra-thin thermal insulating gasket.

[0113] Comparative Example 2

[0114] This comparative example provides a high thermal conductivity ultra-thin silicone gasket, which is prepared by the following method:

[0115] Vinyl silicone oil (500cP) 100 parts, end-hydrogen silicone oil (400-1000mm 2 / s) 22 parts, side hydrogen silicone oil (90-130mm 2 / s) 137 parts, 3,5-dimethyl-1-hexyn-3-ol inhibitor 1 part, tetramethyl divinyl disiloxane platinum complex catalyst 5 parts, black silicone rubber color paste 1 part, antioxidant 1076 4 parts, anionic polymer dispersant 4 parts are added to a rotary stirrer, and stirred at a speed of 900 rpm for 10 minutes to obtain an organic silica gel matrix. Finely screened 2μm aluminum nitride A 820 parts, 30μm aluminum oxide A 1700 parts, 10μm aluminum oxide B 520 parts and 1μm aluminum oxide C 650 parts are added to the organic silica gel matrix, stirred at a speed of 900 rpm for 10-30 minutes, and 40 parts of dodecyl trimethoxy silane are gradually added to obtain a base material. The stirred base material is fully mixed by a three-roll grinder, then placed in a vacuum machine to evacuate the air in the base material, and then placed between release films and calendered by a calender. The base material thickness is pressed to between 0.20mm during the initial pressing, and the base material thickness is controlled to 0.13mm during the secondary calendering. Then, it is formed at 150°C to obtain a high thermal conductivity ultra-thin thermal insulating gasket.

[0116] Comparative Example 3

[0117] This comparative example provides a high thermal conductivity ultra-thin silicone gasket, which is prepared by the following method:

[0118] Vinyl silicone oil (500cP) 100 parts, end-hydrogen silicone oil (400-1000mm 2 / s) 22 parts, side hydrogen silicone oil (90-130mm 2 / s) 137 parts, 3,5-dimethyl-1-hexyn-3-ol inhibitor 1 part, tetramethyl divinyl disiloxane platinum complex catalyst 5 parts, black silicone rubber color paste 1 part, antioxidant 1076 4 parts, anionic polymer dispersant 4 parts are added to a rotary stirrer, and stirred at a speed of 900 rpm for 10 minutes to obtain an organic silica gel matrix. Finely screened 2μm aluminum nitride A 820 parts, 30μm aluminum oxide A 1700 parts, 10μm aluminum oxide B 520 parts and 1μm aluminum oxide C 650 parts are added to the organic silica gel matrix, stirred at a speed of 900 rpm for 10-30 minutes, and 40 parts of KH570 are gradually added to obtain a base material. The stirred base material is fully mixed by a three-roll grinder, then placed in a vacuum machine to evacuate the air in the base material, and then placed between release films and calendered by a calender. The base material thickness is pressed to between 0.20mm during the initial pressing, and the base material thickness is controlled to 0.13mm during the secondary calendering. Then, it is formed at 150°C to obtain a high thermal conductivity ultra-thin thermal insulating gasket.

[0119] Comparative Example 4

[0120] This comparative example provides a high thermal conductivity ultra-thin silicone gasket, which is prepared by the following method:

[0121] Vinyl silicone oil (500cP) 100 parts, end-hydrogen silicone oil (400-1000mm 2 / s) 22 parts, side hydrogen silicone oil (90-130mm 2 / s), 137 parts of 1 part of inhibitor, 5 parts of catalyst, 1 part of black silicone rubber color paste, 4 parts of antioxidant and 4 parts of dispersant were added into a rotary stirrer and stirred at a speed of 900 rpm for 10 minutes to obtain an organic silica gel matrix. 1700 parts of 30 μm aluminum oxide A, 520 parts of 10 μm aluminum oxide B, 820 parts of 2 μm aluminum oxide D and 650 parts of 1 μm aluminum oxide C after fine screening were added into the organic silica gel matrix and stirred at a speed of 900 rpm for 10-30 minutes, and 40 parts of terminal hydroxyl polydimethylsiloxane were gradually added to obtain a base material. The stirred base material is fully mixed by a three-roll grinder, then placed in a vacuum machine to evacuate the air in the base material, and then placed between release films and calendered by a calender. The base material thickness is pressed to between 0.20mm during the initial pressing, and the base material thickness is controlled to 0.13mm during the secondary calendering. Then, it is formed at 150°C to obtain a high thermal conductivity ultra-thin thermal insulating gasket.

[0122] Comparative Example 5

[0123] This comparative example provides a high thermal conductivity ultra-thin silicone gasket, which is prepared by the following method:

[0124] 100 parts of vinyl silicone oil (500cP), 22 parts of end-hydrogen silicone oil (400-1000mm 2 / s), side hydrogenated silicone oil (90-130mm 2 / s), 137 parts of inhibitor, 1 part of catalyst, 1 part of black silicone rubber color paste, 4 parts of antioxidant and 4 parts of dispersant were added into a rotary stirrer and stirred at a speed of 900 rpm for 10 minutes to obtain an organic silica gel matrix. 820 parts of 30 μm aluminum nitride A, 1700 parts of 30 μm aluminum oxide A, 520 parts of 20 μm aluminum oxide B and 650 parts of 90 μm aluminum oxide C were added into the organic silica gel matrix and stirred at a speed of 900 rpm for 10-30 minutes, and 40 parts of terminal hydroxyl polydimethylsiloxane were gradually added to obtain a base material. The stirred base material is fully mixed by a three-roll grinder, then placed in a vacuum machine to evacuate the air in the base material, and then placed between release films and calendered by a calender. The base material thickness is pressed to between 0.20mm during the initial pressing, and the base material thickness is controlled to 0.13mm during the secondary calendering. Then, it is formed at 150°C to obtain a high thermal conductivity ultra-thin thermal insulating gasket.

[0125] Thermal conductivity test: Based on ISO 22007-2 test standard, Hotdisk TPS-3500 thermal conductivity tester.

[0126] Thermal resistance test: Based on ASTM D5470 test standard, LW-9389 thermal conductivity and thermal resistance tester.

[0127] Volatile matter test: 150℃, calculated based on sample weight loss after 24h.

[0128] Table 1: Test data of Examples 1 to 5 and Comparative Examples 1 to 5

[0129] Thermal conductivity W / mK <![CDATA[Thermal resistance °C·in 2 / W]]> Volatile matter% Example 1 7.39 0.110 0.12 Example 2 8.25 0.108 0.15 Example 3 8.15 0.118 0.16 Example 4 3.06 0.363 0.08 Example 5 5.73 0.317 0.09 Comparative Example 1 / / / Comparative Example 2 7.34 0.108 0.64 Comparative Example 3 / / / Comparative Example 4 5.77 0.154 0.12 Comparative Example 5 / / /

[0130] It can be seen from Table 1 that the thermal conductivity of the ultra-thin thermally conductive gasket made by the formula of the present invention can reach above 8 W / mK.

[0131] Compared with Example 1, no modifier was added to Comparative Example 1, resulting in the base material being too dry to make a sample, indicating the role of modified polydimethylsiloxane in improving powder filling. In Comparative Example 3, KH570 was directly added without hydrolysis treatment, and the modification effect was poor, and the base material was too dry to make a sample, indicating the superiority of modified polydimethylsiloxane in the use method. In Comparative Example 2, due to the low boiling point of dodecyltrimethoxysilane, the volatile matter of the modified sample was measured to be much higher than that of the modified polydimethylsiloxane modified sample, indicating the superiority of modified polydimethylsiloxane in reducing material viscosity and improving gasket performance.

[0132] Compared with Example 1, in Comparative Example 4, no aluminum nitride filler was added, and the thermal conductivity of the sample was significantly reduced, indicating the importance of aluminum nitride in improving the thermal conductivity.

[0133] Compared with Example 1, the filler particle sizes in Comparative Example 5 are all larger than 20 μm, there is no small-size powder, the fluidity and fineness of the base material are extremely poor, and the sample cannot be calendered.

[0134] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A high thermal conductivity ultra-thin silicone gasket, characterized in that: The composition comprises, by weight: 100 parts of vinyl silicone oil, 5-30 parts of end hydrogen-containing silicone oil, 100-150 parts of side hydrogen-containing silicone oil, 20-100 parts of modifier, 500-1500 parts of aluminum nitride, 200-3500 parts of aluminum oxide, 0.2-0.4 parts of inhibitor, 0.5-5 parts of catalyst, 4-10 parts of antioxidant, 2-10 parts of dispersant and 0.5-2 parts of optional colorant.

2. The high thermal conductivity ultra-thin silicone gasket according to claim 1, characterized in that: The composition comprises, by weight: 100 parts of vinyl silicone oil, 22 parts of end-hydrogenated silicone oil, 137 parts of side-hydrogenated silicone oil, 40 parts of modifier, 820 parts of aluminum nitride, 2870 parts of aluminum oxide, 0.2-1.5 parts of inhibitor, 5 parts of catalyst, 4 parts of antioxidant, 4 parts of dispersant and 1 part of optional colorant.

3. The high thermal conductivity ultra-thin silicone gasket according to claim 1 or 2, characterized in that: The modifier is at least one of hydroxyl-terminated polydimethylsiloxane, vinyl-terminated polydimethylsiloxane and alkoxy-terminated polydimethylsiloxane.

4. The high thermal conductivity ultra-thin silicone gasket according to claim 1 or 2, characterized in that: The aluminum oxide includes aluminum oxide A, aluminum oxide B and aluminum oxide C; The aluminum oxide A is spherical aluminum oxide with a particle size of 20-40 μm, the aluminum oxide B is single-crystal aluminum oxide with a particle size of 1-20 μm, and the aluminum oxide C is single-crystal aluminum oxide with a particle size of 0.5-1 μm; Optionally, the average particle size of the aluminum nitride is 1-5 μm.

5. The high thermal conductivity ultra-thin silicone gasket according to claim 1 or 2, characterized in that: The viscosity of the vinyl silicone oil is 100-500 cP, and the content of vinyl is 0.5-1.5 wt %; Optionally, the viscosity of the hydrogen-containing silicone oil is 400-1000 mm 2 / s, the hydrogen content accounts for 0.01-0.03% of the weight of the hydrogen-containing silicone oil; Optionally, the viscosity of the side hydrogenated silicone oil is 90-130 mm 2 / s, and the hydrogen content accounts for 0.1-0.3% of the weight of the hydrogen-containing silicone oil.

6. The high thermal conductivity ultra-thin silicone gasket according to claim 1 or 2, characterized in that: The inhibitors include acetylenic alcohol inhibitors; Optionally, the catalyst comprises a platinum catalyst; Optionally, the antioxidant is a hindered phenol antioxidant, preferably one or more of antioxidant 1010, antioxidant 1024 and antioxidant 1076; Optionally, the dispersant includes a polymer dispersant; Optionally, the colorant includes black silicone rubber color paste.

7. The method for preparing the high thermal conductivity ultra-thin silicone gasket according to any one of claims 1 to 6, characterized in that: The steps include: (a) mixing a formulated amount of vinyl silicone oil, terminal hydrogen silicone oil, side hydrogen silicone oil, inhibitor, catalyst, antioxidant, dispersant and optional colorant to prepare an organic silica gel matrix; (b) adding a formula amount of aluminum nitride and aluminum oxide to the organic silica gel matrix and stirring, and adding a formula amount of a modifier during the stirring process to obtain a base material; (c) The base material is calendered and formed to obtain the high thermal conductivity ultra-thin silicone gasket.

8. The preparation method according to claim 7, characterized in that: Before step (c), the method further includes the steps of strengthening mixing of the base material and removing gas; Preferably, a three-roll mill is used to enhance mixing; Preferably, the gas is removed by vacuuming.

9. The preparation method according to claim 7 or 8, characterized in that: In step (c), a primary calendering and a secondary calendering are included; Preferably, the thickness of the base material after the first calendering is 0.20 mm-0.25 mm; Preferably, the thickness of the base material after the secondary calendering is 0.08mm-0.16mm; Optionally, the molding temperature is 120-180°C, preferably 150°C.

10. Use of the high thermal conductivity ultra-thin silicone gasket described in any one of claims 1 to 6 and the high thermal conductivity ultra-thin silicone gasket prepared by the preparation method described in any one of claims 7 to 9 in electronic products.

Citation Information

Patent Citations

  • A thermally conductive and insulating silicone material composed of aluminum nitride and aluminum oxide and its preparation method

    CN111925654B

Cited By

  • Low-volatility heat-conducting gasket and preparation method thereof

    CN121574568A